(untitled) (Scientific journal of the Fergana State University, 2026)
This research article analyzes the theoretical differences between the concepts of language and speech and their roles in linguistic studies. The authors explain, based on scholarly literature, that language is an abstract system of symbols and rules shared socially and culturally by members of a community, whereas speech is the individual and concrete manifestation of this system. The dichotomy of language and speech established by F. de Saussure, as well as the concepts of “competence” and “performance” introduced by N.Chomsky, are examined. The realizations of linguistic units at the levels of language and speech (such as phoneme – phone, lexeme – word, etc.) are demonstrated with examples. In addition, the article discusses the unique interpretation of the essence of language and speech in the works of Alisher Navoiy and the significance of these concepts from the perspective of modern linguistic research. The article emphasizes the intrinsic interconnectedness of language and speech, and scientifically substantiates the necessity of studying them as distinct yet fundamental aspects in theoretical and applied linguistics.